Flexible thin films for solar cells based on cadmium sulfide - Zaitsev, R. V.; Khrypunov, M. G.; Kirichenko, M. V.; Khrypunova, I. V. (НТУ "ХПІ", 2018)
For the purpose of creation of the economic, suitable for large-scale application technology of formation of a layer of wide-scale "window", for thin-film photo-electric converters on the basis of sulfide and telluride of cadmium the pilot studies of temperature effect of a deposition of the films of sulfide of cadmium received by method of magnetron dispersion on a direct current on their optical properties and crystalline structure were conducted. By method of a two-channel optical spectroscopy it is established that a deposition of films of sulfide of cadmium at a temperature of 160 °C allows to form layers with a width of forbidden region of 1,41 eV that approaches value, characteristic of monocrystals, and the density of the photon flux passing through a cadmium sulfide layer in a spectral interval of a photosensitivity of telluride of cadmium at the level of 37,0 W·nm·cm².

З метою створення економічної, придатної для широкомасштабного застосування технології формування шару широкозонного "вікна" для тонкоплівкових фотоелектричних перетворювачів на основі сульфіду та телуриду кадмію були проведені експериментальні дослідження впливу температури осадження плівок сульфіду кадмію, отриманих методом магнетронного розпилення на постійному струмі, на їх оптичні властивості і кристалічну структуру. Методом двоканальної оптичної спектроскопії встановлено, що осадження плівок сульфіду кадмію при температурі 160 °С дозволяє формувати шари з шириною забороненої зони 1,41 еВ, що наближається до значення, характерного для монокристалів, і густиною потоку фотонів, що проходять через шар сульфіду кадмію в спектральному інтервалі фоточутливості телуриду кадмію, на рівні 37,0 Вт·нм·см².
Гнучкі тонкі плівки для сонячних елементів на сульфіді кадмію
Keywords: cadmium sulfide films; optical losses; crystalline structure; photo-electric converters; метод магнетронного розпилення; постійний струм; оптичні втрати; ширина забороненої зони